Effect of adding Red Brick Powder and Polyethylene Terephthalate in Clay. - Eryunaningsih, Ririn Tri; Wulandari, Sri (Jurnal Teknik Sipil, 2024)
Low bearing capacity soil is frequently encountered when designing the construction of civil buildings. It's important to stabilize the soil.. In this study, the effectiveness of PET plastic and red brick powder as clay stabilizers was examined. The silica and alumina oxide included in the red brick powder can bind soil particles to form a compact, stable structure. PET plastic can increase the friction between soil grains and reduce the potential for swelling. Soil samples were taken from Hambalang, Bogor Regency. Data was obtained by conducting soil investigations at the Civil Engineering Laboratory of Gunadarma University using experimental methods. The parameters analyzed were the values of shear strength and consolidation in the original condition and soil samples that had been given a mixture of 0.5% PET plastic and red brick powder with a percentage of 7%, 11%, and 15%. According to research, red brick powder and PET plastic can boost soil strength based on soil shear and consolidation parameters. The percentage of the effective mixture is soil with 0.5% PET plastic and 11% red brick powder, with a rise in shear strength of 259.947%, a drop in consolidation time speed of 64.214%, and a decrease in land of 57.116%.